2018
DOI: 10.1016/j.cophys.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Cell biological mechanisms in regulation of the post-infarction inflammatory response

Abstract: Inflammation plays a crucial role in cardiac repair, but may also extend ischemic injury and contribute to post-infarction remodeling. This review manuscript discusses recent advances in our understanding of the cell biology of the post-infarction inflammatory response. Recently published studies demonstrated that the functional repertoire of inflammatory and reparative cells may extend beyond the roles suggested by traditional teachings. Neutrophils may play an important role in cardiac repair by driving macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 79 publications
0
49
0
4
Order By: Relevance
“…Monocyte and neutrophil migration is regulated by numerous CC and CXC chemokines 13,20 . We performed RNAseq and mined the data to detect CC and CXC chemokines.…”
Section: Cmcs Express CC and Cxc Chemokines Regulating Migration Of Nmentioning
confidence: 99%
“…Monocyte and neutrophil migration is regulated by numerous CC and CXC chemokines 13,20 . We performed RNAseq and mined the data to detect CC and CXC chemokines.…”
Section: Cmcs Express CC and Cxc Chemokines Regulating Migration Of Nmentioning
confidence: 99%
“…Beyond the pro-inflammatory and prohealing subtypes, there is a continuum of functional states, with some macrophages displaying characteristics of both classically defined phenotypes (Mosser and Edwards, 2008). In the infarcted myocardium, the controlled recruitment and activation of monocytes and macrophages is required for orchestrating tissue repair and neoangiogenesis to limit excessive scarring and fibrosis (Frangogiannis, 2018;Swirski and Nahrendorf, 2018). Unbalanced or impaired activation of the cells of the immune system after myocardial ischemia results in maladaptive ventricular dilatation, systolic or diastolic dysfunction and myocardial stiffness (Frangogiannis, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Here, we showed that CHF after MI is accompanied by myocardial inflammation, apoptosis and ventricular remodeling. After MI, inflammatory reactions are triggered by DAMPs, activating macrophages to coordinate inflammation and tissue repair; in addition, macrophages regulate autophagy to exert innate immune function 5,18 . Activating subsequent inflammatory/reparative pathways, the highly inflammatory factors trigger apoptosis in cardiomyocytes, cardiac hypertrophy and stiffness, differentiation of myofibroblasts, collagen accumulation, endothelial dysfunction, and endothelial-to-mesenchymal transition, and ensuing ventricular remodeling and impaired left ventricular function.…”
Section: Discussionmentioning
confidence: 99%